PEOPLE’S WILLINGNESS TO PAY FOR ECOSYSTEM SERVICES: A CASE OF COASTAL WETLAND SYSTEM IN KERALA - Resmi C. Panicker (International Journal of Social Science and Economic Research, 2018)
Anthropogenic activities impact the diversity of organisms found in ecosystems above ground and below ground, and thus influence the provision of ecosystem services. The present paper tries to address the problem of sustainable use of resources in coastal wetlands of Kerala with an example of tourist spot known as Veli, a well-known tourist spot in Thiruvananthapuram city. Studies reveal drastic depletion in fauna and fish species in recent decades. In this context, the present work tries to identify the various eco system services associated with coastal wetlands particularly Veli Wetland System. The study also aims to illuminate the economic value of recreational services provided by the Veli Lake and also the threat from waste disposal to the lake. To identify various ecosystem services offered by Veli wetland, discussion with the stake holders, local communities and other beneficiaries have been done. To illuminate the economic value of recreational services from the Lake, primary data have been collected from 120 tourists of Veli through a structured questionnaire. Tourist’s willingness to pay has been used to find out the economic value of recreation benefits from the Lake. To find out the threat of waste disposal into the Lake, case study method has been used and data have been collected from 60 households including fishermen. The lake system is rapidly getting degraded due to reclamation, input of city drainage, siltation and weed infestation. Consequently, the study suggests to impose a user fee from tourists and households for the optimum management of the ecosystem services.